Central role of soluble adenylyl cyclase and cAMP in sperm physiology - Buffone, Mariano Gabriel (2014)
Cyclic adenosine 3′,5′-monophosphate (cAMP), the first second messenger to be described, plays a central role in cell signaling in a wide variety of cell types. Over the last decades, a wide body of literature addressed the different roles of cAMP in cell physiology, mainly in response to neurotransmitters and hormones. cAMP is synthesized by a wide variety of adenylyl cyclases that can generally be grouped in two types: transmembrane adenylyl cyclase and soluble adenylyl cyclases. In particular, several aspects of sperm physiology are regulated by cAMP produced by a single atypical adenylyl cyclase (Adcy10, aka sAC, SACY). The signature that identifies sAC among other ACs, is their direct stimulation by bicarbonate. The essential nature of cAMP in sperm function has been demonstrated using gain of function as well as loss of function approaches. This review unifies state of the art knowledge of the role of cAMP and those enzymes involved in cAMP signaling pathways required for the acquisition of fertilizing capacity of mammalian sperm. This article is part of a Special Issue entitled: The role of soluble adenylyl cyclase in health and disease.